Recent advances in development of cell-free protein synthesis systems for fast and efficient production of recombinant proteins. Issue 17 (31st July 2018) - Lee, Kyung-Ho; Kim, Dong-Myung
Abstract: Cell-free protein synthesis has emerged in recent years as a powerful tool that can potentially transform the production of recombinant proteins. Cell-free protein synthesis harnesses the synthetic power of living cells while eliminating many of the constraints of traditional cell-based gene expression methods. Due to the lack of physical barriers separating the protein synthesis machinery from the surrounding environment, a cell-free protein synthesis reaction mixture can be directly programmed using diverse genetic material for the instant production of recombinant proteins without complicated cloning procedures. However, a number of issues must be addressed for this technology to be widely accepted as an alternative platform for protein production, including quality-control of translation machinery preparations, and high reagent cost. This review describes recent efforts to make cell-free protein synthesis more affordable and more easily accessible for generic applications. Abstract : This review article surveys recent advances in cell-free protein synthesis technology.